Efektivitas Kamus Saku Tematik Qomusul Jaibi Najwa Tsurayya Terhadap Penguasaan KosaKata Bahasa Arab Bagi Siswa Kelas V Madrasah Ibtidaiyyah / The Effectiveness of Qomusul Jaibi Najwa Tsurayya Thematic Pocket Dictionary on Arabic Vocabulary Mastery for Grade V Students of Madrasah Ibtidaiyyah - Nur Fahmuddin Hanif; Muhammad Afif Amrulloh (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
One of the obstacles that is often encountered is the low willingness to bring a dictionary, and also the lack of teaching materials whose vocabulary is arranged systematically according to sub-themes so that students of elementary madrasahs can more easily understand it. This study aims to test and analyze how effective kutaib najwa tsurayya is in overcoming the problem of mastery of mufradat for students of class V of Madrasah Ibtidaiyyah An-nuur Negara Ratu. The research method used in this study is quantitative like a through an experimental approach. Based on the results of the independent samples test that has been carried out, indicate a significant improvement in vocabolary mastery of Arabic by using qomusul jaibi najwa tsurayya in class V of Madrasah Ibtidaiyyah An-nuur Negara Ratu with a Sig. (2-tailed) value of 0.004 <0.05, which indicates that Ho is rejected and Ha is accepted it’s means that there is an influence in the use of qomusul jaibi najwa tsurayya on improving students' mastery of Arabic vocabulary. Abstrak: Salah satu kendala yang sering di jumpai adalah rendahnya kemauan untuk membawa kamus, dan juga belum ditemukannya bahan ajar yang kosa-kata nya tersusun secara sistematis sesuai sub tema agar siswa atau siswi madrasah ibtidaiyyah lebih mudah dalam memahaminya. Penelitian ini bertujuan untuk menguji dan menganalisis seberapa efektiv qomusul jaibi najwa tsurayya dalam mengatasi masalah penguasaan mufradat bagi siswa atau siswi kelas V Madrasah Ibtidaiyyah An-nuur Negara Ratu. Metode penelitian yang digunakan didalam penelitian ini adalah kuantitatif yaitu melalui pendekatan eksperimen. Bedasarkan hasil uji independent samples test yang telah dilakukan, menunjukan adanya peningkatan penguasaan kosakata bahasa Arab yang signifikan dengan menggunakan qomusul jaibi najwa tsurayya di kelas V Madrasah Ibtidaiyyah An-nuur Negara Ratu dengan didapatkannya nilai Sig. (2-tailed) sebesar 0,004 < 0,05, yang menunjukkan bahwa Ho ditolak dan Ha diterima yang artinya terdapat pengaruh dalam penggunaan qomusul jaibi najwa tsurayya terhadap peningkatan penguasaan kosa kata bahasa Arab siswa.